PENGARUHPERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAANTERHADAPSTRUKTUR MODAL PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wulandari, Dearena Indah; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine and analyze the effect of sales growth and firm size on the capital structure of food and beverages companies listed on the Indonesia Stock Exchange partially and simultaneously. Where the independent variables in this study are sales growth and firm size while the dependent variable is capital structure. The number of samples in this study were 8 companies with quantitative data types. The data used in this study is secondary data derived from the financial statements of food and beverages companies listed on the Indonesia Stock Exchange in 2010-2014. The results of data analysis using multiple linear regression analysis, t test, F test and coefficient of determination. From the results of multiple linear regression analysis both partially and simultaneously shows that the variables of sales growth and firm size do not have an influence and are not significant to the capital structure of food and beverages companies listed on the Indonesia Stock Exchange. Keywords: sales growth, company size and capital structure